An analysis of the economic viability and greenhouse gas emissions reductions resulting from the use of solar water heaters in a typical Brazilian dwelling - Altoé, Leandra; Oliveira Filho, Delly; Carlo, Joyce Correna; Monteiro, Paulo Marcos Barros; Martins, Isabella Theresa Almeida (Latin American Journal of Energy Research, 2021)
Several countries have reduced their energy consumption and greenhouse gas emissions levels in buildings by promulgating laws, formulating standards and instituting certification programs. In this context, Brazil launched an energy efficiency certification for buildings in 2009. This study aimed to analyze the economic viability and potential greenhouse gas emissions reductions associated with the use of solar water heaters in a typical Brazilian dwelling. Solar thermal systems were simulated at different energy efficiency levels and shower water flow rates. It was found that the use of solar water heater, as compared with electric heater without a hot water storage, presented internal return rate of approximately 26% per year, simple payback around 4.5 years; net present value about US 2,194.00 and cost of conserved energy around US 0.12 kWh-1. This study also verified that solar water heater use in a typical Brazilian dwelling reduced emissions compared with electric and gas heating by approximately 95 and 256 kgCO2equivalentyear-1, respectively. The total reduction potential of greenhouse gas emissions by use solar water heaters for the Brazilian residential sector was substantial, around 5.75 million tCO2equivalentyear-1.